Identification of Internal Reference Genes in Peripheral Blood Mononuclear Cells of Cattle Populations Adapted to Hot Arid Normoxia and Cold Arid Hypoxia Environments - Verma, Preeti; Sharma, Ankita; Sodhi, Monika; Tiwari, Manish; Vivek, Prince; Kataria, Ranjit S.; Nirajan, S. K.; Bharti, Vijay K.; Singh, Pawan; Lathwal, S. S.; Sharma, Vishal; Masharing, Nampher; et al. (Frontiers in Genetics, 2022)
For accurate and reliable gene expression, the quantitative real-time polymerase chain reaction data requires normalization with a reference gene expressed constantly under all the experimental conditions being analyzed. Till date, no comparative data on suitable RGs are available for cattle populations reared at cold arid high-altitude hypoxia and hot arid tropical normoxia environment. Therefore, the present study was aimed to assess the expression stability of 10 RGs (GAPDH, RPL4, EEF1A1, RPS9, HPRT1, UXT, HMBS, B2M, RPS15, ACTB) in PBMCs of cattle types from cold arid high-altitude hypoxia and hot arid normoxia environments. Four different statistical algorithms: geNorm, NormFinder, BestKeeper and RefFinder were used to assess the stability of these genes. A total of 30 blood samples were collected; 6 adult heifers each of Ladakhi (LAC), Holstein Frisian crosses (HFX) and 4 of Jersey (JYC) cows from cold arid high-altitude hypoxia environment (Group I) and 5 adult heifers each of Sahiwal (SAC), Karan Fries (KFC), Holstein Friesian (HFC) cows from hot arid normoxia environment (Group II). Combined analysis of group I and group II resulted in identification of panel of RGs like RPS9, RPS15, GAPDH that could act as a useful resource to unravel the accurate transcriptional profile of peripheral blood mononuclear cells of cattle populations adapted to tropical and high-altitude conditions.